ANTHROPOMETRIC CHARACTERISTICS AND INDICES OF FEMALE NATIONAL SOCCER PLAYERS OF THE SLOVAK REPUBLIC (Fiep Bulletin - online, 2014)
This study investigated anthropometric characteristics within a group of elite female soccer players. Author find out anthropometric characteristics of female national soccer players of the Slovak Republic in relation to age (U17, U19, “A” national team) and find out how these characteristics change due to ontogenetic development. There are no clear limits of ideal body shape and body composition for female soccer players. Anthropometry is used to assess and predict performance. The four building blocks or measures used to undertake anthropometric assessment are: age, sex, height, and weight. Each of these variables provides one piece of information about person. When two of these variables are used together they are called an index. Our collection of anthropometric data is for the purpose of a research in which we want to present some outcomes on existence or absence of differences in the indicators and indices of physical development in female national soccer players of the Slovak Republic. Anthropometric variables measured in this study was: height, weight, waist circumference, hip circumference and from measurements derived indices: BMI (Body Mass Index), WHR (Waist to Hip Ratio), WHtR (Waist to Height Ratio), W/H ratio (Waist for Height ratio), H/A (Height for Age), W/A (Weight for Age), Ponderal Index (weight divided by height raised to the power of 3 – corpulence index), ABSI (a body shape index – may correspond to a greater fraction of visceral fat compared to peripheral tissue). When the measurements are used together they can provide important information about person’s status. In this study we present the distribution of body weight, height and body indices by age of female soccer players selected to national teams of Slovak Republic. Acknowledgement: This study is a part of VE GA research grant No. 1/1252/12: “Improvement of identification and selection system of young male talented soccer players for junior national teams in the Slovak Republic and streamlining the content of their training and preparation.”
Keywords: soccer; female national players; anthropometry